Performance Characteristics and Cost Optimization of Self-Compacting Concrete with Industrial Waste Additives to be Used in Agricultural Buildings - Memiş, Selçuk (Turkish Science and Technology Publishing (TURSTEP), 2021)
Self-Compacting Concrete (SCC) is a building material that has gained importance recently because it can easily and spontaneously settle in high buildings, where pouring conditions with frequent reinforcement are difficult. Agricultural structures, on the other hand, are structures that involve many units such as plant and animal barns, storage buildings and residences, and require care in their design and construction. In this study prepared for this purpose, it is used in concrete by replacing marble dust and fly ash with cement in concrete that will be used in agricultural structures. The main factor in these studies is to obtain information about the behavior of KYB with marble powder and fly ash, its fresh properties as well as its effect on durability, as well as to calculate the cost of marble powders in SCC with superplasticizers and similar chemical additives. Within the scope of the study, different ratios of marble powder (MP) and fly ash (FA) mixtures were created instead of OPC 32.5 and OPC 42.5. 100 mm cubic samples were prepared with the prepared mixtures and some of the physical properties of these samples were determined in 3th, 7th and 28th days. Samples were compared with SCC concrete values with traditionally produced references. As a result, it has been determined that the contribution of fly ash to SCC is more effective than the contribution of waste marble powder and can be used as powder material. In terms of cost, it has been observed that it will provide advantages in agricultural structures thanks to the high strengths obtained.
Keywords: fly ash; S; fresh concrete; Agriculture (General); Agriculture; compressive strength; chemical admixture; marble powder; scc; S1-972; 12. Responsible consumption